Molecular Adhesion of a Pilus‐derived Peptide Involved in Pseudomonas aeruginosa Biofilm Formation on non‐polar ZnO Surfaces - Prüßner, Tim; Meinderink, Dennis; Zhu, Siqi; Orive, Alejandro G.; Kielar, Charlotte; Huck, Marten; Steinrück, Hans-Georg; Keller, Adrian; Grundmeier, Guido (Chemistry – A European Journal)
Bacterial colonization and biofilm formation on abiotic surfaces are initiated by the adhesion of peptides and proteins. Understanding the adhesion of such peptides and proteins at a molecular level thus represents an important step toward controlling and suppressing biofilm formation on technological and medical materials. This study investigates the molecular adhesion of a pilus‐derived peptide that facilitates biofilm formation of Pseudomonas aeruginosa, a multidrug‐resistant opportunistic pathogen frequently encountered in healthcare settings. Single‐molecule force spectroscopy (SMFS) was performed on chemically etched ZnO surfaces to gather insights about peptide adsorption force and its kinetics. Metal‐free click chemistry for the fabrication of peptide‐terminated SMFS cantilevers was performed on amine‐terminated gold cantilevers and verified by X‐ray photoelectron spectroscopy (XPS) and polarization‐modulated infrared reflection absorption spectroscopy (PM‐IRRAS). Atomic force microscopy (AFM) and XPS analyses reveal stable topographies and surface chemistries of the substrates that are not affected by SMFS. Rupture events described by the worm‐like chain model (WLC) up to 600 pN were detected for the non‐polar ZnO(11‐20) surfaces. The dissociation barrier energy at zero force ΔG(0), the transition state distance xb and bound‐unbound dissociation rate at zero force koff(0) for the single crystalline substrate indicate that coordination and hydrogen bonds dominate the peptide/surface interaction.
Keywords: General Chemistry; Catalysis; Organic Chemistry

Heterogeneous Structural Evolution of In–Zn–O Thin Films during Annealing - Moffitt, Stephanie L.; Cao, Chuntian; Van Hest, Maikel F. A. M.; Schelhas, Laura T.; Steinrück, Hans-Georg; Toney, Michael F. (The Journal of Physical Chemistry C)
Keywords: Surfaces; Coatings and Films; Physical and Theoretical Chemistry; General Energy; Electronic; Optical and Magnetic Materials

Electrode Potential-Dependent Studies of Protein Adsorption on Ti6Al4V Alloy - Duderija, Belma; González-Orive, Alejandro; Ebbert, Christoph; Neßlinger, Vanessa; Keller, Adrian; Grundmeier, Guido (Molecules)
This article presents the potential-dependent adsorption of two proteins, bovine serum albumin (BSA) and lysozyme (LYZ), on Ti6Al4V alloy at pH 7.4 and 37 °C. The adsorption process was studied on an electropolished alloy under cathodic and anodic overpotentials, compared to the open circuit potential (OCP). To analyze the adsorption process, various complementary interface analytical techniques were employed, including PM-IRRAS (polarization-modulation infrared reflection-absorption spectroscopy), AFM (atomic force microscopy), XPS (X-ray photoelectron spectroscopy), and E-QCM (electrochemical quartz crystal microbalance) measurements. The polarization experiments were conducted within a potential range where charging of the electric double layer dominates, and Faradaic currents can be disregarded. The findings highlight the significant influence of the interfacial charge distribution on the adsorption of BSA and LYZ onto the alloy surface. Furthermore, electrochemical analysis of the protein layers formed under applied overpotentials demonstrated improved corrosion protection properties. These studies provide valuable insights into protein adsorption on titanium alloys under physiological conditions, characterized by varying potentials of the passive alloy.
Keywords: Chemistry (miscellaneous); Analytical Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Molecular Medicine; Drug Discovery; Pharmaceutical Science

Electropolymerization of acrylic acid on steel for enhanced joining by plastic deformation - Duderija, B.; Sahin, F.; Meinderink, D.; Calderón-Gómez, J.C.; Schmidt, H.C.; Homberg, W.; Grundmeier, G.; González-Orive, A. (Journal of Advanced Joining Processes)
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

Salting-Out of DNA Origami Nanostructures by Ammonium Sulfate - Hanke, Marcel; Hansen, Niklas; Chen, Ruiping; Grundmeier, Guido; Fahmy, Karim; Keller, Adrian (International Journal of Molecular Sciences)
DNA origami technology enables the folding of DNA strands into complex nanoscale shapes whose properties and interactions with molecular species often deviate significantly from that of genomic DNA. Here, we investigate the salting-out of different DNA origami shapes by the kosmotropic salt ammonium sulfate that is routinely employed in protein precipitation. We find that centrifugation in the presence of 3 M ammonium sulfate results in notable precipitation of DNA origami nanostructures but not of double-stranded genomic DNA. The precipitated DNA origami nanostructures can be resuspended in ammonium sulfate-free buffer without apparent formation of aggregates or loss of structural integrity. Even though quasi-1D six-helix bundle DNA origami are slightly less susceptible toward salting-out than more compact DNA origami triangles and 24-helix bundles, precipitation and recovery yields appear to be mostly independent of DNA origami shape and superstructure. Exploiting the specificity of ammonium sulfate salting-out for DNA origami nanostructures, we further apply this method to separate DNA origami triangles from genomic DNA fragments in a complex mixture. Our results thus demonstrate the possibility of concentrating and purifying DNA origami nanostructures by ammonium sulfate-induced salting-out.
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Computer Science Applications; Spectroscopy; Molecular Biology; General Medicine; Catalysis

Ammonium enables reversible aqueous Zn battery chemistries by tailoring the interphase - Ma, Lin; Pollard, Travis P.; Zhang, Yong; Schroeder, Marshall A.; Ren, Xiaoming; Han, Kee Sung; Ding, Michael S.; Cresce, Arthur V.; Atwater, Terrill B.; Mars, Julian; Cao, Longsheng; Steinrück, Hans-Georg; et al. (One Earth)
Keywords: Earth and Planetary Sciences (miscellaneous); General Environmental Science

Conformal Pressure and Fast-Charging Li-Ion Batteries - Cao, Chuntian; Steinrück, Hans-Georg; Paul, Partha P; Dunlop, Alison R.; Trask, Stephen E.; Jansen, Andrew; Kasse, Robert M; Thampy, Vivek; Yusuf, Maha; Nelson Weker, Johanna; Shyam, Badri; Subbaraman, Ram; et al. (Journal of The Electrochemical Society)
Abstract Batteries capable of extreme fast-charging (XFC) are a necessity for the deployment of electric vehicles. Material properties of electrodes and electrolytes along with cell parameters such as stack pressure and temperature have coupled, synergistic, and sometimes deleterious effects on fast-charging performance. We develop a new experimental testbed that allows precise and conformal application of electrode stack pressure. We focus on cell capacity degradation using single-layer pouch cells with graphite anodes, LiNi0.5Mn0.3Co0.2O2 (NMC532) cathodes, and carbonate-based electrolyte. In the tested range (10 – 125 psi), cells cycled at higher pressure show higher capacity and less capacity fading. Additionally, Li plating decreases with increasing pressure as observed with scanning electron microscopy (SEM) and optical imaging. While the loss of Li inventory from Li plating is the largest contributor to capacity fade, electrochemical and SEM examination of the NMC cathodes after XFC experiments show increased secondary particle damage at lower pressure. We infer that the better performance at higher pressure is due to more homogenous reactions of active materials across the electrode and less polarization through the electrode thickness. Our study emphasizes the importance of electrode stack pressure in XFC batteries and highlights its subtle role in cell conditions.
Keywords: Materials Chemistry; Electrochemistry; Surfaces; Coatings and Films; Condensed Matter Physics; Renewable Energy; Sustainability and the Environment; Electronic; Optical and Magnetic Materials

Corrosion fatigue behavior of electron beam melted iron in simulated body fluid - Wackenrohr, Steffen; Torrent, Christof Johannes Jaime; Herbst, Sebastian; Nürnberger, Florian; Krooss, Philipp; Ebbert, Christoph; Voigt, Markus; Grundmeier, Guido; Niendorf, Thomas; Maier, Hans Jürgen (npj Materials Degradation)
Abstract Pure iron is very attractive as a biodegradable implant material due to its high biocompatibility. In combination with additive manufacturing, which facilitates great flexibility of the implant design, it is possible to selectively adjust the microstructure of the material in the process, thereby control the corrosion and fatigue behavior. In the present study, conventional hot-rolled (HR) pure iron is compared to pure iron manufactured by electron beam melting (EBM). The microstructure, the corrosion behavior and the fatigue properties were studied comprehensively. The investigated sample conditions showed significant differences in the microstructures that led to changes in corrosion and fatigue properties. The EBM iron showed significantly lower fatigue strength compared to the HR iron. These different fatigue responses were observed under purely mechanical loading as well as with superimposed corrosion influence and are summarized in a model that describes the underlying failure mechanisms.
Keywords: Materials Chemistry; Materials Science (miscellaneous); Chemistry (miscellaneous); Ceramics and Composites

Oxide Modified Iron in Electron Beam Powder Bed Fusion—From Processability to Corrosion Properties - Torrent, Christof J. J.; Krooß, Philipp; Huang, Jingyuan; Voigt, Markus; Ebbert, Christoph; Knust, Steffen; Grundmeier, Guido; Niendorf, Thomas (Alloys)
Additive manufacturing (AM) processes are not solely used where maximum design freedom meets low lot sizes. Direct microstructure design and topology optimization can be realized concomitantly during processing by adjusting the geometry, the material composition, and the solidification behavior of the material considered. However, when complex specific requirements have to be met, a targeted part design is highly challenging. In the field of biodegradable implant surgery, a cytocompatible material of an application-adapted shape has to be characterized by a specific degradation behavior and reliably predictable mechanical properties. For instance, small amounts of oxides can have a significant effect on microstructural development, thus likewise affecting the strength and corrosion behavior of the processed material. In the present study, biocompatible pure Fe was processed using electron powder bed fusion (E-PBF). Two different modifications of the Fe were processed by incorporating Fe oxide and Ce oxide in different proportions in order to assess their impact on the microstructural evolution, the mechanical response and the corrosion behavior. The quasistatic mechanical and chemical properties were analyzed and correlated with the final microstructural appearance.

Environment‐Dependent Stability and Mechanical Properties of DNA Origami Six‐Helix Bundles with Different Crossover Spacings - Xin, Yang; Piskunen, Petteri; Suma, Antonio; Li, Changyong; Ijäs, Heini; Ojasalo, Sofia; Seitz, Iris; Kostiainen, Mauri A.; Grundmeier, Guido; Linko, Veikko; Keller, Adrian (Small)
Keywords: Biomaterials; Biotechnology; General Materials Science; General Chemistry

Influence of hydrogel coatings on corrosion and fatigue of iron in simulated body fluid - Huang, Jingyuan; Voigt, Markus; Wackenrohr, Steffen; Ebbert, Christoph; Keller, Adrian; Maier, Hans Jürgen; Grundmeier, Guido (Materials and Corrosion)
Keywords: Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; Mechanical Engineering; Mechanics of Materials; Environmental Chemistry; Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; Mechanical Engineering; Mechanics of Materials; Environmental Chemistry; Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; Mechanical Engineering; Mechanics of Materials; Environmental Chemistry

Effect of Surface Hydrophobicity on the Adsorption of a Pilus-Derived Adhesin-like Peptide - Yang, Yu; Huang, Jingyuan; Dornbusch, Daniel; Grundmeier, Guido; Fahmy, Karim; Keller, Adrian; Cheung, David L. (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Time-Dependent DNA Origami Denaturation by Guanidinium Chloride, Guanidinium Sulfate, and Guanidinium Thiocyanate - Hanke, Marcel; Hansen, Niklas; Tomm, Emilia; Grundmeier, Guido; Keller, Adrian (International Journal of Molecular Sciences)
Guanidinium (Gdm) undergoes interactions with both hydrophilic and hydrophobic groups and, thus, is a highly potent denaturant of biomolecular structure. However, our molecular understanding of the interaction of Gdm with proteins and DNA is still rather limited. Here, we investigated the denaturation of DNA origami nanostructures by three Gdm salts, i.e., guanidinium chloride (GdmCl), guanidinium sulfate (Gdm2SO4), and guanidinium thiocyanate (GdmSCN), at different temperatures and in dependence of incubation time. Using DNA origami nanostructures as sensors that translate small molecular transitions into nanostructural changes, the denaturing effects of the Gdm salts were directly visualized by atomic force microscopy. GdmSCN was the most potent DNA denaturant, which caused complete DNA origami denaturation at 50 °C already at a concentration of 2 M. Under such harsh conditions, denaturation occurred within the first 15 min of Gdm exposure, whereas much slower kinetics were observed for the more weakly denaturing salt Gdm2SO4 at 25 °C. Lastly, we observed a novel non-monotonous temperature dependence of DNA origami denaturation in Gdm2SO4 with the fraction of intact nanostructures having an intermediate minimum at about 40 °C. Our results, thus, provide further insights into the highly complex Gdm–DNA interaction and underscore the importance of the counteranion species.
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Computer Science Applications; Spectroscopy; Molecular Biology; General Medicine; Catalysis

Multimodal quantification of degradation pathways during extreme fast charging of lithium-ion batteries - McShane, Eric J.; Paul, Partha P.; Tanim, Tanvir R.; Cao, Chuntian; Steinrück, Hans-Georg; Thampy, Vivek; Trask, Stephen E.; Dunlop, Alison R.; Jansen, Andrew N.; Dufek, Eric J.; Toney, Michael F.; Weker, Johanna Nelson; et al. (Journal of Materials Chemistry A)
Using a unique combination of advanced characterization techniques, we identify specific degradation mechanisms and quantify degradative species formed during fast charge cycling of lithium-ion battery pouch cells.
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

Simultaneous neutron and X-ray tomography for visualization of graphite electrode degradation in fast-charged lithium-ion batteries - Yusuf, Maha; LaManna, Jacob M.; Paul, Partha P.; Agyeman-Budu, David N.; Cao, Chuntian; Dunlop, Alison R.; Jansen, Andrew N.; Polzin, Bryant J.; Trask, Stephen E.; Tanim, Tanvir R.; Dufek, Eric J.; Thampy, Vivek; et al. (Cell Reports Physical Science)
Keywords: General Physics and Astronomy; General Energy; General Engineering; General Materials Science; General Chemistry

Genotype-phenotype mapping with polyominos made from DNA origami tiles - Dreher, Yannik; Fichtler, Julius; Karfusehr, Christoph; Jahnke, Kevin; Xin, Yang; Keller, Adrian; Göpfrich, Kerstin (Biophysical Journal)
Keywords: Biophysics

Enhanced corrosion resistance of epoxy-films on ultra-thin SiOx PECVD film coated laser surface melted Al-alloys - Varghese, J.; Vieth, P.; Xie, X.; Grundmeier, Guido (SN Applied Sciences)
Abstract The influence of ultra-thin SiO x plasma deposited films on the corrosion resistance of adhesive films on a laser surface melted 7075 aluminium alloy was investigated by means of complementary techniques in comparison to the just laser surface melted state. Laser surface melting (LSM) was performed using a continuous wave mode at a wavelength of 1064 nm. Ultra-thin plasma polymer films were deposited from a mixture of hexamethyldisilane (HMDSO), oxygen, and argon by means of an audio-frequency glow discharge. The surface morphology and surface chemistry compositions were investigated by employing field emission scanning electron microscopy, energy-dispersive X-ray spectroscopy (EDX), diffuse reflection infrared Fourier transform spectroscopy, and X-ray photoelectron spectroscopy. The corrosion resistance of plasma polymer coated LSM Al-7075 alloy was studied using linear sweep voltammetry and electrochemical impedance spectroscopy in a chloride-containing electrolyte. The electrochemical studies showed an improved corrosion resistance for plasma film-coated alloys compared to the just laser surface melted state. To study the corresponding surface adhesive properties, the samples were coated with an epoxy amine adhesive. 90°-peel test under humid conditions confirmed the improvement of interfacial wet-adhesion corrosion tests showed a strong improvement of the delamination resistance of adhesives caused by the ultra-thin interfacial SiO x -films.
Keywords: General Earth and Planetary Sciences; General Physics and Astronomy; General Engineering; General Environmental Science; General Materials Science; General Chemical Engineering

Influence of surface activation on the microporosity of PE‐CVD and PE‐ALD SiO x thin films on PDMS - Hoppe, Christian; Mitschker, Felix; Mai, Lukas; Liedke, Maciej Oskar; Arcos, Teresa; Awakowicz, Peter; Devi, Anjana; Attallah, Ahmed Gamal; Butterling, Maik; Wagner, Andreas; Grundmeier, Guido (Plasma Processes and Polymers)
Keywords: Polymers and Plastics; Condensed Matter Physics

High‐Resolution Study of Changes in Morphology and Chemistry of Cylindrical PS‐ b ‐PMMA Block Copolymer Nanomasks during Mask Development - Bürger, Julius; Venugopal, Harikrishnan; Kool, Daniel; de los Arcos, Teresa; Gonzalez Orive, Alejandro; Grundmeier, Guido; Brassat, Katharina; Lindner, Jörg K.N. (Advanced Materials Interfaces)
Keywords: General Medicine

Combined in-situ attenuated total reflection-Fourier transform infrared spectroscopy and single molecule force studies of poly(acrylic acid) at electrolyte/oxide interfaces at acidic pH - Neßlinger, Vanessa; Orive, Alejandro G.; Meinderink, Dennis; Grundmeier, Guido (Journal of Colloid and Interface Science)
Keywords: Colloid and Surface Chemistry; Surfaces; Coatings and Films; Biomaterials; Electronic; Optical and Magnetic Materials

Comparative analysis of hexamethyldisiloxane and hexamethyldisilazane plasma polymer thin films before and after plasma oxidation - Xie, Xiaofan; de los Arcos, Teresa; Grundmeier, Guido (Plasma Processes and Polymers)
Keywords: Polymers and Plastics; Condensed Matter Physics

The HSP40 chaperone Ydj1 drives amyloid beta 42 toxicity - Ring, Julia; Tadic, Jelena; Ristic, Selena; Poglitsch, Michael; Bergmann, Martina; Radic, Nemanja; Mossmann, Dirk; Liang, YongTian; Maglione, Marta; Jerkovic, Andrea; Hajiraissi, Roozbeh; Hanke, Marcel; et al. (EMBO Molecular Medicine)
Keywords: Molecular Medicine

Anion-specific structure and stability of guanidinium-bound DNA origami - Hanke, Marcel; Dornbusch, Daniel; Hadlich, Christoph; Rossberg, Andre; Hansen, Niklas; Grundmeier, Guido; Tsushima, Satoru; Keller, Adrian; Fahmy, Karim (Computational and Structural Biotechnology Journal)
Keywords: Computer Science Applications; Genetics; Biochemistry; Structural Biology; Biophysics; Biotechnology

Combined Effects of Uniform Applied Pressure and Electrolyte Additives in Lithium-Metal Batteries - Kasse, Robert M.; Geise, Natalie R.; Sebti, Elias; Lim, Kipil; Takacs, Christopher J.; Cao, Chuntian; Steinrück, Hans-Georg; Toney, Michael F. (ACS Applied Energy Materials)
Keywords: Electrical and Electronic Engineering; Materials Chemistry; Electrochemistry; Energy Engineering and Power Technology; Chemical Engineering (miscellaneous)

Direct visualization of the drug loading of single DNA origami nanostructures by AFM-IR nanospectroscopy - Hanke, Marcel; Grundmeier, Guido; Keller, Adrian (Nanoscale)
The efficient loading of DNA nanostructures with intercalating or groove-binding drugs is an important prerequisite for various applications in drug delivery. However, unambiguous verification and quantification of successful drug loading...
Keywords: General Materials Science

Giant Orbital Anisotropy with Strong Spin–Orbit Coupling Established at the Pseudomorphic Interface of the Co/Pd Superlattice - Kim, Sanghoon; Pathak, Sachin; Rhim, Sonny H.; Cha, Jongin; Jekal, Soyoung; Hong, Soon Cheol; Lee, Hyun Hwi; Park, Sung‐Hun; Lee, Han‐Koo; Park, Jae‐Hoon; Lee, Soogil; Steinrück, Hans-Georg; et al. (Advanced Science)
Keywords: General Physics and Astronomy; General Engineering; Biochemistry; Genetics and Molecular Biology (miscellaneous); General Materials Science; General Chemical Engineering; Medicine (miscellaneous)

Nano-FTIR and chemical force analysis of electrografted aryldiazonium salts on ODT-microcontact printed Au-surfaces - Su, Jiangling; González Orive, Alejandro; Grundmeier, Guido (Applied Surface Science)
Keywords: Surfaces; Coatings and Films; Condensed Matter Physics; Surfaces and Interfaces; General Physics and Astronomy; General Chemistry

Oxidation stability of chromium aluminum oxynitride hard coatings - Bobzin, K.; Kalscheuer, C.; Grundmeier, Guido; de los Arcos, T.; Kollmann, S.; Carlet, M. (Surface and Coatings Technology)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Surfaces and Interfaces; Condensed Matter Physics; General Chemistry

Thin Organic‐Inorganic Anti‐Fouling Hybrid‐Films for Microreactor Components - Neßlinger, Vanessa; Welzel, Stefan; Rieker, Florian; Meinderink, Dennis; Nieken, Ulrich; Grundmeier, Guido (Macromolecular Reaction Engineering)
Keywords: Polymers and Plastics; General Chemical Engineering; General Chemistry

Influence of surface activation on the microporosity of PE‐CVD and PE‐ALD SiO x thin films on PDMS - Hoppe, Christian; Mitschker, Felix; Mai, Lukas; Liedke, Maciej Oskar; de los Arcos de Pedro, Maria Teresa; Awakowicz, Peter; Devi, Anjana; Attallah, Ahmed Gamal; Butterling, Maik; Wagner, Andreas; Grundmeier, Guido (Plasma Processes and Polymers)
Keywords: Polymers and Plastics; Condensed Matter Physics

Challenges in the interpretation of gas core levels for the determination of gas-solid interactions within dielectric porous films by ambient pressure XPS - de los Arcos de Pedro, Maria Teresa; Weinberger, Christian; Zysk, Frederik; Raj Damerla, Varun; Kollmann, Sabrina; Vieth, Pascal; Tiemann, Michael; Kühne, Thomas D.; Grundmeier, Guido (Applied Surface Science)
Keywords: Surfaces; Coatings and Films; Condensed Matter Physics; Surfaces and Interfaces; General Physics and Astronomy; General Chemistry

Comparative analysis of hexamethyldisiloxane and hexamethyldisilazane plasma polymer thin films before and after plasma oxidation - Xie, Xiaofan; de los Arcos de Pedro, Maria Teresa; Grundmeier, Guido (Plasma Processes and Polymers)
Keywords: Polymers and Plastics; Condensed Matter Physics

Tuning of antifouling active PDMS domains tethered to epoxy/amine surface - Dogan, Deniz; Ruthmann, Simon; Seewald, Oliver; Bremser, Wolfgang (Progress in Organic Coatings)
Keywords: Materials Chemistry; Organic Chemistry; Surfaces; Coatings and Films; General Chemical Engineering

Reversible functionalization and exfoliation of graphite by a Diels–Alder reaction with furfuryl amine - Torkaman, Najmeh Filvan; Kley, Marina; Bremser, Wolfgang; Wilhelm, René (RSC Advances)
Furfuryl amine-functionalized few-layered graphene was prepared via a mechanochemical process by a [4 + 2] cycloaddition under solvent-free conditions.
Keywords: General Chemical Engineering; General Chemistry

Challenges in the interpretation of gas core levels for the determination of gas-solid interactions within dielectric porous films by ambient pressure XPS - de los Arcos, Teresa; Weinberger, Christian; Zysk, Frederik; Raj Damerla, Varun; Kollmann, Sabrina; Vieth, Pascal; Tiemann, Michael; Kühne, Thomas; Grundmeier, Guido (Applied Surface Science)
Near ambient pressure XPS in nitrogen atmosphere was utilized to investigate gas-solid interactions within porous SiO2 films ranging from 30 to 75 nm thickness. The films were differentiated in terms of porosity and roughness. The XPS N1s core levels of the N2 gas in presence of the SiO2 samples showed variations in width, binding energy and line shape. The width correlated with the surface charge induced in the dielectric films upon X-ray irradiation. The observed different binding energies observed for the N1s peak can only partly be associated with intrinsic work function differences between the samples, opening the possibility that the effect of physisorption at room temperature could be detected by a shift in the measured binding energy. However, the signals also show an increasing asymmetry with rising surface charge. This might be associated with the formation of vertical electrical gradients within the dielectric porous thin films, which complicates the assignment of binding energy positions to specific surface-related effects. With the support of Monte Carlo and first principles density functional theory calculations, the observed shifts were discussed in terms of the possible formation of transitory dipoles upon N2 physisorption within the porous SiO2 films.
Keywords: Surfaces; Coatings and Films; Condensed Matter Physics; Surfaces and Interfaces; General Physics and Astronomy; General Chemistry

Electrochemical performance of KTiOAsO_4 (KTA) in potassium-ion batteries from density-functional theory - Bocchini, Adriana; Gerstmann, Uwe; Bartley, Tim; Steinrück, Hans-Georg; Henkel, Gerald; Schmidt, Wolf Gero (Phys. Rev. Materials)

FeMn with Phases of a Degradable Ag Alloy for Residue-Free and Adapted Bioresorbability - Krüger, Jan Tobias; Hoyer, Kay-Peter; Huang, Jingyuan; Filor, Viviane; Mateus-Vargas, Rafael Hernan; Oltmanns, Hilke; Meißner, Jessica; Grundmeier, Guido; Schaper, Mirko (Journal of Functional Biomaterials)
The development of bioresorbable materials for temporary implantation enables progress in medical technology. Iron (Fe)-based degradable materials are biocompatible and exhibit good mechanical properties, but their degradation rate is low. Aside from alloying with Manganese (Mn), the creation of phases with high electrochemical potential such as silver (Ag) phases to cause the anodic dissolution of FeMn is promising. However, to enable residue-free dissolution, the Ag needs to be modified. This concern is addressed, as FeMn modified with a degradable Ag-Calcium-Lanthanum (AgCaLa) alloy is investigated. The electrochemical properties and the degradation behavior are determined via a static immersion test. The local differences in electrochemical potential increase the degradation rate (low pH values), and the formation of gaps around the Ag phases (neutral pH values) demonstrates the benefit of the strategy. Nevertheless, the formation of corrosion-inhibiting layers avoids an increased degradation rate under a neutral pH value. The complete bioresorption of the material is possible since the phases of the degradable AgCaLa alloy dissolve after the FeMn matrix. Cell viability tests reveal biocompatibility, and the antibacterial activity of the degradation supernatant is observed. Thus, FeMn modified with degradable AgCaLa phases is promising as a bioresorbable material if corrosion-inhibiting layers can be diminished.
Keywords: Biomedical Engineering; Biomaterials

Enhancement of the delamination resistance of adhesive film coated surface laser melted aluminum 7075-T6 alloy by aminophosphonic acid adsorption - Vieth, P.; Garthe, M.-A.; Voswinkel, Dietrich; Schaper, Mirko; Grundmeier, Guido (Surface and Coatings Technology)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Surfaces and Interfaces; Condensed Matter Physics; General Chemistry

Influence of proteins on the corrosion of a conventional and selective laser beam melted FeMn alloy in physiological electrolytes - Huang, Jingyuan; Orive, Alejandro Gonzalez; Krüger, Jan Tobias; Hoyer, Kay-Peter; Keller, Adrian; Grundmeier, Guido (Corrosion Science)
Keywords: General Materials Science; General Chemical Engineering; General Chemistry

Microstructure and corrosion properties of PBF-LB produced carbide nanoparticles additivated AlSi10Mg parts - Kusoglu, Ihsan Murat; Vieth, Pascal; Heiland, Steffen; Huber, Florian; Lüddecke, Arne; Ziefuss, Anna Rosa; Kwade, Arno; Schmidt, Michael; Schaper, Mirko; Barcikowski, Stephan; Grundmeier, Guido (Procedia CIRP)
Keywords: General Medicine

A mechanistic study of the dopant-induced breakdown in halide perovskites using solid state energy storage devices - Mathieson, Angus G. M.; Dose, Wesley M.; Steinrück, Hans-Georg; Takacs, Christopher J.; Feldmann, Sascha; Pandya, Raj; Merryweather, Alice J.; Mackanic, David; Rao, Akshay; Deschler, Felix; De Volder, Michael (Energy & Environmental Science)
Elucidating and quantifying the effects of doping on halide perovskites using lithium ion batteries.
Keywords: Pollution; Nuclear Energy and Engineering; Renewable Energy; Sustainability and the Environment; Environmental Chemistry

Oxidation stability of chromium aluminum oxynitride hard coatings - Bobzin, K.; Kalscheuer, C.; Grundmeier, Guido; Kollmann, S.; Carlet, M.; de los Arcos de Pedro, Maria Teresa (Surface and Coatings Technology)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Surfaces and Interfaces; Condensed Matter Physics; General Chemistry

Electrografting of BTSE: Zn films for advanced steel-aluminum joining by plastic deformation - Duderija, B.; González-Orive, A.; Schmidt, H.C.; Calderón, J.C.; Hordych, I.; Maier, H.J.; Homberg, W.; Grundmeier, G. (Journal of Advanced Joining Processes)
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

Untersuchung von Klebverbindungen für Batteriegehäuse - Schmolke, Tobias; Meschut, Gerson; Rieker, Florian; Meinderink, Dennis; Grundmeier, Guido (adhäsion KLEBEN & DICHTEN)

Water or Anion? Uncovering the Zn2+ Solvation Environment in Mixed Zn(TFSI)2 and LiTFSI Water-in-Salt Electrolytes - Zhang, Yong; Wan, Gang; Lewis, Nicholas H. C.; Mars, Julian; Bone, Sharon E.; Steinrück, Hans-Georg; Lukatskaya, Maria R.; Weadock, Nicholas J.; Bajdich, Michal; Borodin, Oleg; Tokmakoff, Andrei; Toney, Michael F.; et al. (ACS Energy Letters)

Quantification of Efficiency in Lithium Metal Negative Electrodes via Operando X-ray Diffraction - Geise, Natalie R.; Kasse, Robert M.; Nelson Weker, Johanna; Steinrück, Hans-Georg; Toney, Michael F. (Chemistry of Materials)

Toward Unraveling the Origin of Lithium Fluoride in the Solid Electrolyte Interphase - Cao, Chuntian; Pollard, Travis P.; Borodin, Oleg; Mars, Julian E.; Tsao, Yuchi; Lukatskaya, Maria R.; Kasse, Robert M.; Schroeder, Marshall A.; Xu, Kang; Toney, Michael F.; Steinrück, Hans-Georg (Chemistry of Materials)

Zinc Anodizing: Structural Diversity of Anodic Zinc Oxide Controlled by the Type of Electrolyte - Engelkemeier, Katja; Sun, Aijia; Voswinkel, Dietrich; Grydin, Olexandr; Schaper, Mirko; Bremser, Wolfgang (ChemElectroChem)

General relationship between salt concentration and x-ray absorption for binary electrolytes - Steinrück, Hans-Georg (AIP Advances)

Self-Assembled Fibrinogen Hydro- and Aerogels with Fibrin-like 3D Structures - Hense, Dominik; Büngeler, Anne; Kollmann, Fabian; Hanke, Marcel; Orive, Alejandro; Keller, Adrian; Grundmeier, Guido; Huber, Klaus; Strube, Oliver I. (Biomacromolecules)

Morphological Dynamics of Leukemia Cells on TiO2 Nanoparticle Coatings Studied by AFM - Garcia Diosa, Jaime Andres; Gonzalez Orive, Alejandro; Grundmeier, Guido; Camargo Amado, Ruben Jesus; Keller, Adrian (Applied Sciences)
Coatings of modified TiO2 nanoparticles (TiO2-m) have been shown to effectively and selectively trap non-adherent cancer cells, with an enormous potential for applications in photodynamic therapy (PDT). Leukemia cells have a remarkable affinity for TiO2-m coatings, adhering to the surface by membrane structures and exhibiting morphologic characteristics of amoeboid locomotion. However, the details of the cell–substrate interaction induced by the TiO2-m coating remain elusive. With the aim to obtain a better understanding of this phenomenon, leukemia cell adhesion to such coatings was characterized by atomic force microscopy (AFM) for short contact times up to 60 min. The cell and membrane morphological parameters mean cell height, contact area, cell volume, and membrane roughness were determined at different contact times. These results reveal cell expansion and contraction phases occurring during the initial stage of adhesion. Subsequently, the leukemic cells reach what appears to be a new resting state, characterized by pinning of the cell membrane by TiO2-m nanoparticle aggregates protruding from the coating surface.

Influence of thickness, homogeneity, and morphology of TiO2-m nanoparticle coatings on cancer cell adhesion - Garcia-Diosa, Jaime Andrés; Orive, Alejandro Gonzalez; Grundmeier, Guido; Keller, Adrian; Camargo-Amado, Rubén Jesús (Surface and Coatings Technology)

Using In Situ High-Energy X-ray Diffraction to Quantify Electrode Behavior of Li-Ion Batteries from Extreme Fast Charging - Paul, Partha P.; Cao, Chuntian; Thampy, Vivek; Steinrück, Hans-Georg; Tanim, Tanvir R.; Dunlop, Alison R.; Trask, Stephen E.; Jansen, Andrew N.; Dufek, Eric J.; Nelson Weker, Johanna; Toney, Michael F. (ACS Applied Energy Materials)

Unraveling the Unconventional Order of a High-Mobility Indacenodithiophene–Benzothiadiazole Copolymer - Cendra, Camila; Balhorn, Luke; Zhang, Weimin; O’Hara, Kathryn; Bruening, Karsten; Tassone, Christopher J.; Steinrück, Hans-Georg; Liang, Mengning; Toney, Michael F.; McCulloch, Iain; Chabinyc, Michael L.; Salleo, Alberto; et al. (ACS Macro Letters)

Visualization of dynamic polaronic strain fields in hybrid lead halide perovskites - Guzelturk, Burak; Winkler, Thomas; Van de Goor, Tim W. J.; Smith, Matthew D.; Bourelle, Sean A.; Feldmann, Sascha; Trigo, Mariano; Teitelbaum, Samuel W.; Steinrück, Hans-Georg; de la Pena, Gilberto A.; Alonso-Mori, Roberto; Zhu, Diling; et al. (Nature Materials)

A Review of Existing and Emerging Methods for Lithium Detection and Characterization in Li‐Ion and Li‐Metal Batteries - Paul, Partha P.; McShane, Eric J.; Colclasure, Andrew M.; Balsara, Nitash; Brown, David E.; Cao, Chuntian; Chen, Bor‐Rong; Chinnam, Parameswara R.; Cui, Yi; Dufek, Eric J.; Finegan, Donal P.; Gillard, Samuel; et al. (Advanced Energy Materials)

Modeling cyclic voltammetry during solid electrolyte interphase formation: Baseline scenario of a dynamically evolving tunneling barrier resulting from a homogeneous single-phase insulating film - Steinrück, Hans-Georg (The Journal of Chemical Physics)

Water-in-Salt LiTFSI Aqueous Electrolytes. 1. Liquid Structure from Combined Molecular Dynamics Simulation and Experimental Studies - Zhang, Yong; Lewis, Nicholas H. C.; Mars, Julian; Wan, Gang; Weadock, Nicholas J.; Takacs, Christopher J.; Lukatskaya, Maria R.; Steinrück, Hans-Georg; Toney, Michael F.; Tokmakoff, Andrei; Maginn, Edward J. (The Journal of Physical Chemistry B)

Oligothiophene Phosphonic Acids for Self-Assembled Monolayer Field-Effect Transistors - Zhao, Baolin; Gothe, Bastian; Groh, Arthur; Schmaltz, Thomas; Will, Johannes; Steinrück, Hans-Georg; Unruh, Tobias; Mecking, Stefan; Halik, Marcus (ACS Applied Materials & Interfaces)

Lamellar carbon-aluminosilicate nanocomposites with macroscopic orientation - Paripović, Dragana; Hartmann, Lucia; Steinrück, Hans-Georg; Magerl, Andreas; Li-Destri, Giovanni; Fontana, Yannik; Fontcuberta i Morral, Anna; Oveisi, Emad; Bomal, Enzo; Frauenrath, Holger (Nanoscale)
A liquid-crystalline hexaphenylene amphiphile and an aluminosilicate precursor were co-assembled and pyrolyzed to form carbon-aluminosilicate nanocomposites with controlled lamellar orientation and macroscopic order.

Quantification of heterogeneous, irreversible lithium plating in extreme fast charging of lithium-ion batteries - Paul, Partha P.; Thampy, Vivek; Cao, Chuntian; Steinrück, Hans-Georg; Tanim, Tanvir R.; Dunlop, Alison R.; Dufek, Eric J.; Trask, Stephen E.; Jansen, Andrew N.; Toney, Michael F.; Nelson Weker, Johanna (Energy & Environmental Science)
Realization of extreme fast charging (XFC, ≤15 minutes) of lithium-ion batteries is imperative for the widespread adoption of electric vehicles.

Orientation-Dependent Distortion of Lamellae in a Block Copolymer Electrolyte under DC Polarization - Galluzzo, Michael D.; Grundy, Lorena S.; Takacs, Christopher J.; Cao, Chuntian; Steinrück, Hans-Georg; Fu, Sean; Rivas Valadez, Michael A.; Toney, Michael F.; Balsara, Nitash P. (Macromolecules)

Nanoscale Surface Topography Modulates hIAPP Aggregation Pathways at Solid–Liquid Interfaces - Hanke, Marcel; Yang, Yu; Ji, Yuxin; Grundmeier, Guido; Keller, Adrian (International Journal of Molecular Sciences)
The effects that solid–liquid interfaces exert on the aggregation of proteins and peptides are of high relevance for various fields of basic and applied research, ranging from molecular biology and biomedicine to nanotechnology. While the influence of surface chemistry has received a lot of attention in this context, the role of surface topography has mostly been neglected so far. In this work, therefore, we investigate the aggregation of the type 2 diabetes-associated peptide hormone hIAPP in contact with flat and nanopatterned silicon oxide surfaces. The nanopatterned surfaces are produced by ion beam irradiation, resulting in well-defined anisotropic ripple patterns with heights and periodicities of about 1.5 and 30 nm, respectively. Using time-lapse atomic force microscopy, the morphology of the hIAPP aggregates is characterized quantitatively. Aggregation results in both amorphous aggregates and amyloid fibrils, with the presence of the nanopatterns leading to retarded fibrillization and stronger amorphous aggregation. This is attributed to structural differences in the amorphous aggregates formed at the nanopatterned surface, which result in a lower propensity for nucleating amyloid fibrillization. Our results demonstrate that nanoscale surface topography may modulate peptide and protein aggregation pathways in complex and intricate ways.

Unraveling the interaction between doxorubicin and DNA origami nanostructures for customizable chemotherapeutic drug release - Ijäs, Heini; Shen, Boxuan; Heuer-Jungemann, Amelie; Keller, Adrian; Kostiainen, Mauri A; Liedl, Tim; Ihalainen, Janne A; Linko, Veikko (Nucleic Acids Research)
Abstract Doxorubicin (DOX) is a common drug in cancer chemotherapy, and its high DNA-binding affinity can be harnessed in preparing DOX-loaded DNA nanostructures for targeted delivery and therapeutics. Although DOX has been widely studied, the existing literature of DOX-loaded DNA-carriers remains limited and incoherent. Here, based on an in-depth spectroscopic analysis, we characterize and optimize the DOX loading into different 2D and 3D scaffolded DNA origami nanostructures (DONs). In our experimental conditions, all DONs show similar DOX binding capacities (one DOX molecule per two to three base pairs), and the binding equilibrium is reached within seconds, remarkably faster than previously acknowledged. To characterize drug release profiles, DON degradation and DOX release from the complexes upon DNase I digestion was studied. For the employed DONs, the relative doses (DOX molecules released per unit time) may vary by two orders of magnitude depending on the DON superstructure. In addition, we identify DOX aggregation mechanisms and spectral changes linked to pH, magnesium, and DOX concentration. These features have been largely ignored in experimenting with DNA nanostructures, but are probably the major sources of the incoherence of the experimental results so far. Therefore, we believe this work can act as a guide to tailoring the release profiles and developing better drug delivery systems based on DNA-carriers.

Scaling Up DNA Origami Lattice Assembly. - Xin, Y; Shen, B; Kostiainen, MA; Grundmeier, Guido; Castro, M; Linko, V; Keller, Adrian (Chemistry – A European Journal)

Protein Adsorption at Nanorough Titanium Oxide Surfaces: The Importance of Surface Statistical Parameters beyond Surface Roughness. - Yang, Y; Knust, S; Schwiderek, S; Qin, Q; Yun, Q; Grundmeier, Guido; Keller, Adrian (Nanomaterials)

Biotemplated Lithography of Inorganic Nanostructures (BLIN) for Versatile Patterning of Functional Materials - Piskunen, Petteri; Shen, Boxuan; Keller, Adrian; Toppari, J. Jussi; Kostiainen, Mauri A.; Linko, Veikko (ACS Applied Nano Materials)

DNA Nanostructures in the Fight Against Infectious Diseases. - Smith, DM; Keller, Adrian (Advanced NanoBiomed Research)

Adsorption of SARS-CoV-2 Spike Protein S1 at Oxide Surfaces Studied by High-Speed Atomic Force Microscopy. - Xin, Y; Grundmeier, Guido; Keller, Adrian (Advanced NanoBiomed Research)

Effect of nanoscale surface topography on the adsorption of globular proteins - Yang, Yu; Yu, Mingrui; Böke, Frederik; Qin, Qin; Hübner, René; Knust, Steffen; Schwiderek, Sabrina; Grundmeier, Guido; Fischer, Horst; Keller, Adrian (Applied Surface Science)

Effect of PAA-induced surface etching on the adhesion properties of ZnO nanostructured films - Meinderink, Dennis; Kielar, C.; Sobol, O.; Ruhm, L.; Rieker, F.; Nolkemper, K.; Orive, A.G.; Ozcan, O.; Grundmeier, Guido (International Journal of Adhesion and Adhesives)

In situ backside Raman spectroscopy of zinc oxide nanorods in an atmospheric‐pressure dielectric barrier discharge plasma - Knust, Steffen; Ruhm, Lukas; Kuhlmann, Andreas; Meinderink, Dennis; Bürger, Julius; Lindner, Jörg K. N.; Arcos de Pedro, Maria Teresa; Grundmeier, Guido (Journal of Raman Spectroscopy)

Ion Beam Nanopatterning of Biomaterial Surfaces - Yang, Yu; Keller, Adrian (Applied Sciences)
Ion beam irradiation of solid surfaces may result in the self-organized formation of well-defined topographic nanopatterns. Depending on the irradiation conditions and the material properties, isotropic or anisotropic patterns of differently shaped features may be obtained. Most intriguingly, the periodicities of these patterns can be adjusted in the range between less than twenty and several hundred nanometers, which covers the dimensions of many cellular and extracellular features. However, even though ion beam nanopatterning has been studied for several decades and is nowadays widely employed in the fabrication of functional surfaces, it has found its way into the biomaterials field only recently. This review provides a brief overview of the basics of ion beam nanopatterning, emphasizes aspects of particular relevance for biomaterials applications, and summarizes a number of recent studies that investigated the effects of such nanopatterned surfaces on the adsorption of biomolecules and the response of adhering cells. Finally, promising future directions and potential translational challenges are identified.

Enhanced corrosion resistance of adhesive/galvanised steel interfaces by nanocrystalline ZnO thin film deposition and molecular adhesion promoting films - Grothe, Richard; Striewe, Jan Andre; Meinderink, Dennis; Tröster, Thomas; Grundmeier, Guido (The Journal of Adhesion)

Strain-Dependent Adsorption of Pseudomonas aeruginosa-Derived Adhesin-like Peptides at Abiotic Surfaces - Yang, Yu; Schwiderek, Sabrina; Grundmeier, Guido; Keller, Adrian (Micro)
Implant-associated infections are an increasingly severe burden on healthcare systems worldwide and many research activities currently focus on inhibiting microbial colonization of biomedically relevant surfaces. To obtain molecular-level understanding of the involved processes and interactions, we investigate the adsorption of synthetic adhesin-like peptide sequences derived from the type IV pili of the Pseudomonas aeruginosa strains PAK and PAO at abiotic model surfaces, i.e., Au, SiO2, and oxidized Ti. These peptides correspond to the sequences of the receptor-binding domain 128–144 of the major pilin protein, which is known to facilitate P. aeruginosa adhesion at biotic and abiotic surfaces. Using quartz crystal microbalance with dissipation monitoring (QCM-D), we find that peptide adsorption is material- as well as strain-dependent. At the Au surface, PAO(128–144) shows drastically stronger adsorption than PAK(128–144), whereas adsorption of both peptides is markedly reduced at the oxide surfaces with less drastic differences between the two sequences. These observations suggest that peptide adsorption is influenced by not only the peptide sequence, but also peptide conformation. Our results furthermore highlight the importance of molecular-level investigations to understand and ultimately control microbial colonization of surfaces.

Magnesium-Free Immobilization of DNA Origami Nanostructures at Mica Surfaces for Atomic Force Microscopy - Xin, Yang; Zargariantabrizi, Amir Ardalan; Grundmeier, Guido; Keller, Adrian (Molecules)
DNA origami nanostructures (DONs) are promising substrates for the single-molecule investigation of biomolecular reactions and dynamics by in situ atomic force microscopy (AFM). For this, they are typically immobilized on mica substrates by adding millimolar concentrations of Mg2+ ions to the sample solution, which enable the adsorption of the negatively charged DONs at the like-charged mica surface. These non-physiological Mg2+ concentrations, however, present a serious limitation in such experiments as they may interfere with the reactions and processes under investigation. Therefore, we here evaluate three approaches to efficiently immobilize DONs at mica surfaces under essentially Mg2+-free conditions. These approaches rely on the pre-adsorption of different multivalent cations, i.e., Ni2+, poly-l-lysine (PLL), and spermidine (Spdn). DON adsorption is studied in phosphate-buffered saline (PBS) and pure water. In general, Ni2+ shows the worst performance with heavily deformed DONs. For 2D DON triangles, adsorption at PLL- and in particular Spdn-modified mica may outperform even Mg2+-mediated adsorption in terms of surface coverage, depending on the employed solution. For 3D six-helix bundles, less pronounced differences between the individual strategies are observed. Our results provide some general guidance for the immobilization of DONs at mica surfaces under Mg2+-free conditions and may aid future in situ AFM studies.

Entwicklung einer Methode zur Bewertung einer stahlintensiven Mischbau-Klebverbindung eines Batteriegehäuses gegenüber mechanischer und medialer Belastung und Berücksichtigung der Interphasenstruktur - Schmolke, Tobias; Teutenberg, Dominik; Meschut, Gerson; Meinderink, Dennis; Koch, Leon; Ebbert, Christoph; Grundmeier, Guido

Durability of nanolayer Ti–Al–O–N hard coatings under simulated polycarbonate melt processing conditions - Brögelmann, T; Bobzin, K; Grundmeier, Guido; de los Arcos, T; Kruppe, N C; Schwiderek, S; Carlet, M (Journal of Physics D: Applied Physics)
Keywords: Surfaces; Coatings and Films; Acoustics and Ultrasonics; Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Atomic Layer Deposition of Copper Metal Films from Cu(acac) 2 and Hydroquinone Reductant - Tripathi, Tripurari Sharan; Wilken, Martin; Hoppe, Christian; de los Arcos, Teresa; Grundmeier, Guido; Devi, Anjana; Karppinen, Maarit (Advanced Engineering Materials)
Keywords: Condensed Matter Physics; General Materials Science

Review of infrared spectroscopy techniques for the determination of internal structure in thin SiO2 films - de los Arcos de Pedro, Maria Teresa; Müller, Hendrik; Wang, Fuzeng; Damerla, Varun Raj; Hoppe, Christian; Weinberger, Christian; Tiemann, Michael; Grundmeier, Guido (Vibrational Spectroscopy)

Design of a TiAlON multilayer coating: Oxidation stability and deformation behavior - Bobzin, K.; Kalscheuer, C.; Grundmeier, G.; de los Arcos de Pedro, Maria Teresa; Schwiderek, S.; Carlet, M. (Surface and Coatings Technology)

In situ backside Raman spectroscopy of zinc oxide nanorods in an atmospheric‐pressure dielectric barrier discharge plasma - Knust, Steffen; Ruhm, Lukas; Kuhlmann, Andreas; Meinderink, Dennis; Bürger, Julius; Lindner, Jörg K. N.; de los Arcos de Pedro, Maria Teresa; Grundmeier, Guido (Journal of Raman Spectroscopy)

Thermostable water reservoirs in the interlayer space of a sodium hectorite clay through the intercalation of γ-aminopropyl(dimethyl)ethoxysilane in toluene - Keil, Waldemar; Zhao, Kai; Oswald, Arthur; Bremser, Wolfgang; Schmidt, Claudia; Hintze-Bruening, Horst (Physical Chemistry Chemical Physics)
Thermostable compartmentalized sodium-water sites through intercalated γ-aminopropyl-dimethyl-ethoxy silane in synthetic hectorite.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Review of infrared spectroscopy techniques for the determination of internal structure in thin SiO2 films - de los Arcos, Teresa; Müller, Hendrik; Wang, Fuzeng; Damerla, Varun Raj; Hoppe, Christian; Weinberger, Christian; Tiemann, Michael; Grundmeier, Guido (Vibrational Spectroscopy)
A comparison of infrared spectroscopic analytical approaches was made in order to assess their applicability for internal structure characterization of SiO2 thin films. Markers for porosity and/or disorder based on the analysis of the asymmetric stretching absorption band of SiO2 between 900−1350 cm−1 were discussed. The shape of this band, which shows a well-defined LO–TO splitting, depends not only on the inherent characteristics of the film under analysis but also on the particular geometry of the IR experiment and the specific surface selection rules of the substrate. Three types of SiO2 thin films with clearly defined porosity ranging from dense films to mesoporous films were investigated by transmission (at different incidence angles), direct specular reflection (at different angles), and diffuse reflection. Two different types of substrate, metallic and semiconducting, were used. The combined effect of substrate and specific technique in the final shape of the band, was discussed, and the efficacy for their applicability to the determination of porosity in thin SiO2 films was critically evaluated.

TiO2 nanoparticle coatings on glass surfaces for the selective trapping of leukemia cells from peripheral blood - Garcia Diosa, Jaime Andres; Gonzalez Orive, Alejandro; Weinberger, Christian; Schwiderek, Sabrina; Knust, Steffen; Tiemann, Michael; Grundmeier, Guido; Keller, Adrian; Camargo Amado, Ruben Jesus (Journal of Biomedical Materials Research Part B: Applied Biomaterials)
Photodynamic therapy (PDT) using TiO2 nanoparticles has become an important alternative treatment for different types of cancer due to their high photocatalytic activity and high absorption of UV-A light. To potentiate this treatment, we have coated commercial glass plates with TiO2 nanoparticles prepared by the sol–gel method (TiO2-m), which exhibit a remarkable selectivity for the irreversible trapping of cancer cells. The physicochemical properties of the deposited TiO2-m nanoparticle coatings have been characterized by a number of complementary surface-analytical techniques and their interaction with leukemia and healthy blood cells were investigated. Scanning electron and atomic force microscopy verify the formation of a compact layer of TiO2-m nanoparticles. The particles are predominantly in the anatase phase and have hydroxyl-terminated surfaces as revealed by Raman, X-ray photoelectron, and infrared spectroscopy, as well as X-ray diffraction. We find that lymphoblastic leukemia cells adhere to the TiO2-m coating and undergo amoeboid-like migration, whereas lymphocytic cells show distinctly weaker interactions with the coating. This evidences the potential of this nanomaterial coating to selectively trap cancer cells and renders it a promising candidate for the development of future prototypes of PDT devices for the treatment of leukemia and other types of cancers with non-adherent cells.

Zinc Anodizing: Structural Diversity of Anodic Zinc Oxide Controlled by the Type of Electrolyte - Engelkemeier, Katja; Sun, Aijia; Voswinkel, Dietrich; Grydin, Olexandr; Schaper, Mirko; Bremser, Wolfgang (ChemElectroChem)

Analytical characterization of polyamide 11 used in the context of selective laser sintering: Physico-chemical correlations - Scherer, Beate; Kottenstedde, Ingo Leonard; Bremser, Wolfgang; Matysik, Frank-Michael (Polymer Testing)

GIWAXS-SIIRkit: scattering intensity, indexing and refraction calculation toolkit for grazing-incidence wide-angle X-ray scattering of organic materials - Savikhin, Victoria; Steinrück, Hans-Georg; Liang, Ru-Ze; Collins, Brian A.; Oosterhout, Stefan D.; Beaujuge, Pierre M.; Toney, Michael F. (Journal of Applied Crystallography)
Grazing-incidence wide-angle X-ray scattering (GIWAXS) has become an increasingly popular technique for quantitative structural characterization and comparison of thin films. For this purpose, accurate intensity normalization and peak position determination are crucial. At present, few tools exist to estimate the uncertainties of these measurements. Here, a simulation package is introduced called GIWAXS-SIIRkit , where SIIR stands for scattering intensity, indexing and refraction. The package contains several tools that are freely available for download and can be executed in MATLAB. The package includes three functionalities: estimation of the relative scattering intensity and the corresponding uncertainty based on experimental setup and sample dimensions; extraction and indexing of peak positions to approximate the crystal structure of organic materials starting from calibrated GIWAXS patterns; and analysis of the effects of refraction on peak positions. Each tool is based on a graphical user interface and designed to have a short learning curve. A user guide is provided with detailed usage instruction, tips for adding functionality and customization, and exemplary files.

Crystallization and Organic Field‐Effect Transistor Performance of a Hydrogen‐Bonded Quaterthiophene - Gebers, Jan; Özen, Bilal; Hartmann, Lucia; Schaer, Michel; Suàrez, Stéphane; Bugnon, Philippe; Scopelliti, Rosario; Steinrück, Hans-Georg; Konovalov, Oleg; Magerl, Andreas; Brinkmann, Martin; Petraglia, Riccardo; et al. (Chemistry – A European Journal)

Impact of Processing on Structural and Compositional Evolution in Mixed Metal Halide Perovskites during Film Formation - Abdelsamie, Maged; Xu, Junwei; Bruening, Karsten; Tassone, Christopher J.; Steinrück, Hans-Georg; Toney, Michael F. (Advanced Functional Materials)

Heterogeneous Behavior of Lithium Plating during Extreme Fast Charging - Tanim, Tanvir R.; Paul, Partha P.; Thampy, Vivek; Cao, Chuntian; Steinrück, Hans-Georg; Nelson Weker, Johanna; Toney, Michael F.; Dufek, Eric J.; Evans, Michael C.; Jansen, Andrew N.; Polzin, Bryant J.; Dunlop, Alison R.; et al. (Cell Reports Physical Science)

Advanced Characterization in Clean Water Technologies - Bone, Sharon E.; Steinrück, Hans-Georg; Toney, Michael F. (Joule)

Understanding additive controlled lithium morphology in lithium metal batteries - Kasse, Robert M.; Geise, Natalie R.; Ko, Jesse S.; Nelson Weker, Johanna; Steinrück, Hans-Georg; Toney, Michael F. (Journal of Materials Chemistry A)
Investigation of the mechanisms underlying control of electrodeposited lithium metal morphology using electrolyte additives in lithium metal batteries.

Time‐Resolved Structural Kinetics of an Organic Mixed Ionic–Electronic Conductor - Paulsen, Bryan D.; Wu, Ruiheng; Takacs, Christopher J.; Steinrück, Hans-Georg; Strzalka, Joseph; Zhang, Qingteng; Toney, Michael F.; Rivnay, Jonathan (Advanced Materials)

Interfacial Speciation Determines Interfacial Chemistry: X‐ray‐Induced Lithium Fluoride Formation from Water‐in‐salt Electrolytes on Solid Surfaces - Steinrück, Hans-Georg; Cao, Chuntian; Lukatskaya, Maria R.; Takacs, Christopher J.; Wan, Gang; Mackanic, David G.; Tsao, Yuchi; Zhao, Jingbo; Helms, Brett A.; Xu, Kang; Borodin, Oleg; Wishart, James F.; et al. (Angewandte Chemie International Edition)

Concentration and velocity profiles in a polymeric lithium-ion battery electrolyte - Steinrück, Hans-Georg; Takacs, Christopher J.; Kim, Hong-Keun; Mackanic, David G.; Holladay, Benjamin; Cao, Chuntian; Narayanan, Suresh; Dufresne, Eric M.; Chushkin, Yuriy; Ruta, Beatrice; Zontone, Federico; Will, Johannes; et al. (Energy & Environmental Science)
Direct measurements of concentration and velocity profiles in a polymeric lithium-ion battery electrolyte provide insights into the transference number.

Interface between Water–Solvent Mixtures and a Hydrophobic Surface - Prihoda, Annemarie; Will, Johannes; Duchstein, Patrick; Becit, Bahanur; Lossin, Felix; Schindler, Torben; Berlinghof, Marvin; Steinrück, Hans-Georg; Bertram, Florian; Zahn, Dirk; Unruh, Tobias (Langmuir)

Tortuosity Effects in Lithium-Metal Host Anodes - Chen, Hao; Pei, Allen; Wan, Jiayu; Lin, Dingchang; Vilá, Rafael; Wang, Hongxia; Mackanic, David; Steinrück, Hans-Georg; Huang, William; Li, Yuzhang; Yang, Ankun; Xie, Jin; et al. (Joule)

Toward quantifying capacity losses due to solid electrolyte interphase evolution in silicon thin film batteries - Steinrück, Hans-Georg; Cao, Chuntian; Veith, Gabriel M.; Toney, Michael F. (The Journal of Chemical Physics)

Effect of DNA Origami Nanostructures on hIAPP Aggregation - Hanke, Marcel; Gonzalez Orive, Alejandro; Grundmeier, Guido; Keller, Adrian (Nanomaterials)
The aggregation of human islet amyloid polypeptide (hIAPP) plays a major role in the pathogenesis of type 2 diabetes mellitus (T2DM), and numerous strategies for controlling hIAPP aggregation have been investigated so far. In particular, several organic and inorganic nanoparticles (NPs) have shown the potential to influence the aggregation of hIAPP and other amyloidogenic proteins and peptides. In addition to conventional NPs, DNA nanostructures are receiving more and more attention from the biomedical field. Therefore, in this work, we investigated the effects of two different DNA origami nanostructures on hIAPP aggregation. To this end, we employed in situ turbidity measurements and ex situ atomic force microscopy (AFM). The turbidity measurements revealed a retarding effect of the DNA nanostructures on hIAPP aggregation, while the AFM results showed the co-aggregation of hIAPP with the DNA origami nanostructures into hybrid peptide–DNA aggregates. We assume that this was caused by strong electrostatic interactions between the negatively charged DNA origami nanostructures and the positively charged peptide. Most intriguingly, the influence of the DNA origami nanostructures on hIAPP aggregation differed from that of genomic double-stranded DNA (dsDNA) and appeared to depend on DNA origami superstructure. DNA origami nanostructures may thus represent a novel route for modulating amyloid aggregation in vivo.